PENGGUNAAN PUPUK KCL DAN BOKASHI PADA TANAMAN UBI JALAR (Ipomae batatas) - Daniel Arief Sianturi; Ernita Ernita (DINAMIKA PERTANIAN, 2014)
This research aim to know the effect of KCl and bokashi on yield of sweet potato. The research was conducted at the experiment farm Faculty of agriculture Riau Islamic university Pekanbau from March to June 2013. The completely randomized design with two factorials was used. The first factor consisted of various doses of KCL fertilizer (K); without KCl, 5 g/planting bed, 10 g/planting bed, and 15 g/planting bed. The second factor consisted of various bokashi dosages; without bokashi, 50 g/plant, 100 g/plant, and 150 g/plant. Data were analyzed statistically according to F and BNJ tests at the 5% significance level. Interaction between KCL fertilizer and bokashi for sweet potato had a significant effect on sweet potato weight per tuber with the best treatment of 15 g/panting bed of KCl and 150 g/plant of bokashi. KCl fertilizer affected significantly on number of tuber per plant, tuber weight per tuber, tuber weight per plant, and dry material weight with the best treatment of 15 kg/panting bed. The use of bokashi also showed a significant effect on number of tuber per plant, tube weight per tuber, tuber weight per plant, and dry material weight with the best treatment of 150 g/plant.